PENGEMBANGAN BAHAN AJAR IPS BERBASIS PENDEKATAN SAINS TEKNOLOGI MASYARAKAT (STM) UNTUK MENINGKATKAN KREATIVITAS SISWA DI SEKOLAH DASAR - Sitti Jauhar (Universitas Negeri Makassar, 2018)
Social Sciences (IPS) as a part of education has an important role in improving the quality of education, especially in producing qualified students, namely humans who are able to think critically, creatively, logically, and take the initiative in responding to issues in society caused by the impact of scientific development knowledge / science and technology (science and technology). However, social studies learning in elementary schools today is less associated with social and technological issues in the community. Especially related to the development of technology and the presence of technology products in the community, as well as the consequences thereof. Social studies teaching in schools is solely oriented to the demands of the curriculum. A teacher is not easy to create conditions conducive to all students. There are students who are proactive, there are students who are not talkative (quiet) but have academic abilities, and there are also students who talk a lot but have low abilities. In fact, there are students with middle to lower academic abilities who feel pressured by social science material that is full of theories, concepts, which are complicated and even difficult to understand. This causes the lack of meaning in social studies at this time, thus causing student learning activities to be low and learning to be passive. In fact, the 2013 curriculum, the teaching approach used in learning activities should be positioned as a center of attention or in other words active students. Development of IPS teaching materials using the STM approach is a form of teaching that not only emphasizes the mastery of science concepts but also emphasizes the role of science and technology in various people's lives and fosters a sense of social responsibility towards the impact of science and technology on the community. Through the Community Science approach, 6 domains of science can be developed, namely the realm of concepts, processes, creativity, attitudes, applications, and interrelations.